Oncological Surgery During the COVID‐19 Pandemic: The Need for Deep and Lasting Measures. (23rd June 2020) - Souadka, Amine; Benkabbou, Amine; Majbar, Mohammed Anass; Essangri, Hajar; Amrani, Laila; Mohsine, Raouf; Ghannam, Abdelilah; El Ahmadi, Brahim; Belkhadir, Zakaria
Abstract : The COVID‐19 pandemic has overwhelmed health system capacity and affected cancer centers worldwide. This letter to the editor proposes the need to prepare for a long‐lasting battle.